2018
DOI: 10.1186/s12985-018-1071-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enzyme-linked immunosorbent assay systems using rift valley fever virus nucleocapsid protein and inactivated virus as antigens

Abstract: BackgroundRift Valley Fever (RVF) is a mosquito-borne viral zoonosis. To detect RVF virus (RVFV) infection, indirect immunoglobulin G (IgG) and immunoglobulin M (IgM) enzyme linked immunosorbent assays (ELISAs) which utilize recombinant RVFV nucleocapsid (RVFV-N) protein as assay antigen, have reportedly been used, however, there is still a need to develop more sensitive and specific methods of detection.MethodsRVFV-N protein was expressed in Escherichia coli (E. coli) and purified by histidine-tag based affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The diagnostic accuracy estimates determined in our study are similar to those previously published for ELISAs based on a whole RVFV antigen [36][37][38][39][40][41]55] as well as those based on recombinant NP ELISAs [51][52][53][54][55][56][57][58][59][60], including the commercially available NP-based competition ELISAs [52,60]. Although recorded at a relatively low rate, false-positive results were documented in this study across different subpopulations and are of particular concern in ruminants originating from RVF-non-endemic countries.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The diagnostic accuracy estimates determined in our study are similar to those previously published for ELISAs based on a whole RVFV antigen [36][37][38][39][40][41]55] as well as those based on recombinant NP ELISAs [51][52][53][54][55][56][57][58][59][60], including the commercially available NP-based competition ELISAs [52,60]. Although recorded at a relatively low rate, false-positive results were documented in this study across different subpopulations and are of particular concern in ruminants originating from RVF-non-endemic countries.…”
Section: Discussionsupporting
confidence: 87%
“…Antigenic cross-reactivity studies using sera from experimentally infected sheep demonstrated that antibodies induced by African phleboviruses other than RVFV should not confuse serodiagnosis of RVF [ 78 ]. RVFV rNP-based I-ELISA has been reported to not cross-react with sera from mice experimentally infected with different viruses of genus Phlebovirus , Nairovirus and Orthobunyavirus [ 57 ]. Other advantages of RVFV rNP-based I-ELISA, including cost-effectiveness of rNP antigen production, have been previously discussed [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant nucleocapsid protein has been used for the serodiagnosis of several viruses, such as SARS-CoV [ 27 , 35 ], MERS-CoV [ 36 ], severe fever with thrombocytopenia syndrome virus (SFTSV) [ 37 , 38 ], Rift Valley fever virus [ 39 ], Nipah virus [ 40 ], and SARS-CoV-2 [ 41 , 42 , 43 , 44 ]. Although SARS-CoV-2 immunoassays and point-of-care assays are appearing in the market, comparative performance data are urgently needed for laboratory diagnosis and the public health response to COVID-19 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the study include the need to test using methods commonly used for high-throughput diagnostics, such as ELISA and fluorescence microsphere immunoassays. Such assays have been developed for diagnoses of RVFV [ 20 , 21 , 22 , 23 , 24 ], but none are currently commercially available in the United States. Examination and testing of NP amino acid coding sequence for regions of shared antigenic identity would be helpful in developing specific assays.…”
Section: Discussionmentioning
confidence: 99%